2011
DOI: 10.1107/s0108768111013814
|View full text |Cite
|
Sign up to set email alerts
|

Modulated anharmonic ADPs are intrinsic to aperiodic crystals: a case study on incommensurate Rb2ZnCl4

Abstract: The superspace maximum entropy method (MEM) density in combination with structure refinements has been used to uncover the modulation in incommensurate Rb2ZnCl4 close to the lock-in transition. Modulated atomic displacement parameters (ADPs) and modulated anharmonic ADPs are found to form an intrinsic part of the modulation. Refined values for the displacement modulation function depend on the presence or absence of modulated ADPs in the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…The reproduction of the myogenesis process from mammalian embryonic skeletal muscle cells was demonstrated, as previously reported in both in vivo and in vitro studies [ 45 - 47 ]. It is well known that cadherin plays important roles in morphogenesis, such as cell recognition and cell rearrangement including myogenesis, both in the embryo and in the adult organism during regeneration [ 20 , 43 , 48 ].…”
Section: Discussionsupporting
confidence: 73%
“…The reproduction of the myogenesis process from mammalian embryonic skeletal muscle cells was demonstrated, as previously reported in both in vivo and in vitro studies [ 45 - 47 ]. It is well known that cadherin plays important roles in morphogenesis, such as cell recognition and cell rearrangement including myogenesis, both in the embryo and in the adult organism during regeneration [ 20 , 43 , 48 ].…”
Section: Discussionsupporting
confidence: 73%
“…Both harmonic and unharmonic ADP modulations have been attempted, according to model from Li et. al.,26 similar results can be obtained by refining ADPs by 4 harmonic waves combined with 2 unharmonic waves, and refining ADPs by 6 harmonic waves. Further inclusion of unharmonic ADP modulation can significantly reduce the R factor, but is in expense of bond valence summations.…”
supporting
confidence: 79%
“…It can be concluded that EDMA is able to calculate the properties of critical points and atomic basins with very good accuracy. The original version of EDMA has been used to determine the atomic positions (atomic modulation functions) of aperiodic [LaS] 1:14 [NbS 2 ] and Rb 2 ZnCl 4 (van Smaalen et al, 2003;Li et al, 2011). Properties at BCPs and ionic charges (number of atoms in atomic basins) have been determined for several amino acids and tripeptides (Netzel et al, 2008;Netzel & van Smaalen, 2009).…”
Section: Validation Of Edmamentioning
confidence: 99%